Utilidad de los tratamientos para neumonía por Covid 19, mediante revisión sistemática de literatura y meta-análisis - Tapullima Paima, Teddy Luis (2022)
Five drugs that have been widely used in the treatment of covid-19 were evaluated through a systematic review of the literature and meta-analysis in order to assess their usefulness as part of the therapy. Hydroxychloroquine does not reduce the severity of symptoms in covid-19 patients. Azithromycin does not improve the clinical results of covid-19 patients. In regard to Enoxaparin, patients with moderate or severe disease benefit from anticoagulation, reducing mortality from this disease. However is not useful in mild cases, in which it should not be used. Dexamethasone resulted in lower 28-day mortality among those receiving mechanical ventilation, but not among those who breathed on their own (did not require mechanical ventilation). The available reliable evidence does not support the use of Ivermectin for the treatment or prevention of covid-19 outside of well[1]designed randomized trials. Faced with health situations such as epidemic outbreaks in which the treatment to be provided in order to safeguard the life of vulnerable populations is not clear, an adequate way to define the usefulness of therapeutic schemes is the systemic reviews of the literature and meta-analysis.